1975
DOI: 10.1136/adc.50.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis in children with recurrent abdominal pain.

Abstract: . Long-term prognosis in children with recurrent abdominal pain. The present study is a follow-up of 34 cases admitted to a paediatric department with recurrent abdominal pain (RAP) in 1942 and 1943. 45 persons without a history of RAP were selected at random and included as controls. Using a questionnaire, there was a higher incidence of gastrointestinal symptoms among persons with a history of RAP during childhood than among controls (P < 0 05). 18 of the original 34 cases who still had symptoms were re-exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
88
1
6

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(96 citation statements)
references
References 9 publications
1
88
1
6
Order By: Relevance
“…Some children with persistent abdominal pain also report a variety of additional symptoms including headaches, fatigue, dizziness, and nonspecific somatic complaints (Oster, 1972), suggesting the possibility of a somatization disorder (Ernst et al, 1984;Walker et al, 1991). Moreover, abdominal pain and associated somatic symptoms can have a considerable impact on children's daily functioning both academically and socially (Claar et al, 1999).Prospective studies have shown that many children with abdominal pain continue to complain of somatic symptoms and disability years after their initial evaluation (Apley and Hale, 1973;Christensen and Mortensen, 1975;Magni et al, 1987;Stickler and Murphy, 1979;Walker et al, 1995Walker et al, , 1998. For any patient population, however, the average longitudinal trajectory rarely describes all individuals.…”
mentioning
confidence: 99%
“…Some children with persistent abdominal pain also report a variety of additional symptoms including headaches, fatigue, dizziness, and nonspecific somatic complaints (Oster, 1972), suggesting the possibility of a somatization disorder (Ernst et al, 1984;Walker et al, 1991). Moreover, abdominal pain and associated somatic symptoms can have a considerable impact on children's daily functioning both academically and socially (Claar et al, 1999).Prospective studies have shown that many children with abdominal pain continue to complain of somatic symptoms and disability years after their initial evaluation (Apley and Hale, 1973;Christensen and Mortensen, 1975;Magni et al, 1987;Stickler and Murphy, 1979;Walker et al, 1995Walker et al, , 1998. For any patient population, however, the average longitudinal trajectory rarely describes all individuals.…”
mentioning
confidence: 99%
“…4 -6 With this approach, approximately 30% to 40% of children do have resolution of their pain. 7,8 However, the remainder continue to exhibit symptoms and go on to be adults with abdominal pain, anxiety, or other somatic disorders. 9 Pharmaceutical treatments are commonly used in an effort to manage symptoms despite the lack of data supporting their efficacy.…”
mentioning
confidence: 99%
“…26 Implications of pediatric RAP across the lifespan are not well understood. Early follow-up studies reported persistence of recurrent abdominal pain into adulthood for one third to one half of affected children, 24,27,28 but are limited by the lack of standardized assessments and formal diagnostic criteria, and none used any formal assessment of psychopathology. In more recent studies using standardized assessments and control groups, former RAP patients reported significantly greater abdominal pain, other somatic symptoms, functional impairment, health service use, and internalizing psychiatric symptoms in comparison to controls at 5-year follow-up, and females with a history of RAP were significantly more likely to meet diagnostic criteria for IBS.…”
mentioning
confidence: 99%